Ocular Hypertension Following Intravitreal Injection of 0.7mg Dexamethasone Implant versus 2mg Triamcinolone. (17th February 2020) - Kuley, Brandon; Storey, Philip P.; Pancholy, Maitri; Obeid, Anthony; Murphy, James; Goodman, Jake; Wibbelsman, Turner D.; Regillo, Carl; Chiang, Allen
ABSTRACT: Background : To compare the incidence and outcomes of ocular hypertension (OHT) after intravitreal injection of 0.7 mg dexamethasone (DEX) and 2 mg triamcinolone acetonide (IVT). Methods : In a single-center, retrospective comparative case series, all patients with at least 3 months follow-up receiving 2 mg IVT 3/1/2012 – 3/1/2017 or 0.7 mg dexamethasone 10/1/2014 – 3/1/2017 were included. Ocular hypertension was defined as an intraocular pressure (IOP) ≥ 25 mmHg. Patients with a minimum of 3 months follow-up were included. Patients receiving any other form of topical, oral, or intravitreal steroid were excluded. Results : 106 eyes in 100 patients receiving IVT and 114 eyes in 102 patients receiving DEX were included. The mean number of injections was 2.9 for patients receiving IVT and 2.4 for patients receiving DEX ( p = .11). Fourteen eyes (13.2%) in 14 patients receiving IVT developed OHT compared to 17 eyes (15.1%) in 15 patients receiving DEX ( p = .85). All cases of OHT were managed with IOP lowering drops or observation alone. Conclusions : Rates of ocular hypertension following 2 mg IVT and DEX are similar. All patients developing OHT were successfully managed without surgical intervention.